Flexible Prices and Leverage - Francesco D'Acunto; Ryan Liu; Carolin Pflueger; Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2017)
The frequency with which firms adjust output prices helps explain persistent differences in capital structure across firms. Unconditionally, the most exible-price firms have a 19% higher long-term leverage ratio than the most sticky-price firms, controlling for known determinants of capital structure. Sticky-price firms increased leverage more than exible-price firms following the staggered implementation of the Interstate Banking and Branching Efficiency Act across states and over time, which we use in a difference-in-differences strategy. Firms' frequency of price adjustment did not change around the deregulation.
Keywords: E12; E44; G28; G32; G33; 330; capital structure; nominal rigidities; bank deregulation; industrial organization and finance; price setting; bankruptcy